Contribution of spanish artist Pablo Picasso into development of graphics - Apele, Diāna (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Pablo Picasso belongs to the creators of modern Western culture in the first half of the 20th century. He has the same recognition and popularity as the writer J. Joyce, architect Le Corbusier, composer I. Stravinsky, actor Ch. Chaplin without whom the culture of that period is not imaginable. Picasso has been successfully working in painting, applying various graphical techniques, making sculptures, performing in monumental painting, making theatre decorations, making and decorating ceramics, writing plays, poems, stories, and being an outstanding drawer (Conzen, 2005). Pablo Picasso has left significant traces in the history of art, to a large extent he has been one of the key figures in the processes determining what the modern of art of that specific period should be. Picasso has influenced many artists directly or indirectly – the followers of Western schools and local artists in Latvia. The key topic of this research is graphics, having deeper analysis of the creative works of Picasso the author has chosen to explore Picasso as a graphic artist who excelled in such graphic techniques as flat printing (lithography), deep printing (etching, engraving, aquatint, mezzotint, dry needle ), letterpress printing (wood carving, woodcut, linocut) and others. The artist has been noted by an extremely variable manner – it was typical for him start each new work as individual entirety experimenting with graphical forms, colors, textures, lines, volumes, playing with the contrasts of light and dark and emotional atmosphere. Picasso has applied the elements of his arsenal in diverse variations: compositional schemes and proportions. Creating pieces of art Picasso revealed the technical and visual lexis typical only for him. Picasso has left many works in the linocut technique. It cannot be asserted for sure that Pablo has invented this technique, but he has tried to master all possible ways provided by this technique devoting numerous hours to it. Colorful linoengravings created in the 1960s are considered to be small masterpieces in the history of the world art. Technical means applied in this graphical technique ensure a great generalization degree of a graphical image. Works done in linocut concentrate great, expressive power, express the intensity of searches for content and form. The live process of the linocut technique is vivacious, changing, with its own development and mutual symbiosis are felt. Picasso has left permanent footprints in the art history, has been one of the most significant artists in the processes determining what the modern art of that time should be. Picasso’s contribution into the development of art is irreplaceable and is not completely estimated. Picasso has influenced many people – his contemporaries, modern followers of Western schools, and also the artists here, in Latvia. Picasso’s contribution into the development of graphics is irreplaceable from the view of history of culture. The artist has left many works in the linocut technique, colourful lino-engravings created in the 1960s; in the history of world art there are considered to be masterpieces. The aim of the research: to describe the artistic contribution of Picasso into development of graphics and to analyze his contribution into the linocut technique. The methods of the research: exploration of theoretical literature and Internet resources. The theoretical background of the research: Ikšelis, A. B. (2010), Conzen, I. (2005), Kačalova, T., Pētersons, R. (2005), Židels, A. (2002), Žilo, F., Leiks, K. (1991), Эренбург, И. Г., Алпатов, М. В. (1967).